Powerful Disruptions: Braceros, Campesinos, and the Green Revolution in Mexico, 1940–1965 - Chávez Leyva, José Miguel (Agricultural History, 2021)
Abstract: [None available but on the disruption of peasant economies in Mexico from the 1940s and the impact on the Bracera Program.]
Number: 3